Pengaruh Piutang Murabahah terhadap Laba Bersih Bank Syariah Indonesia (BSI) Periode 2021-2022 - Ii Badriati; Dona Ramadhan (STEBI Global Mulia Cikarang, 2023)
Bank Syariah Indonesia, which is known by the public, is a financial institution that oversees sharia principles. On February 1, 2021 Bank Syariah Indonesia (BSI) was the result of the merger of Bank Syariah Mandiri, Bank BRI Syariah and Bank BNI Syariah. At the same time, Bank Syariah Indonesia (BSI) released its developer product, namely murabahah financing. Murabaha financing objects whose development tends to increase from time to time. On the basis of seeing an increase in murabahah financing every year the author wants to know whether this increase has an effect on net profit at Bank Syariah Indonesia (BSI). The purpose of this research is to find out and partially describe murabahah receivables on net profit at Bank Syariah Indonesia (BSI) for the 2021-2022 period. This study uses the product theory from Adiwarman A. Karim (2008) which states that murabaha financing is the sale and purchase of goods at the original price with additional profits agreed between the bank and the customer and the net profit theory from (Kasmir, 2014) which states net profit as the difference between revenue minus costs incurred for business purposes and minus taxes. This research method is a quantitative method with secondary time series data, namely the monthly reports of Bank Syariah Indonesia (BSI) for the 2021-2022 period. Sampling using purposive sampling technique. Analyzed with the classical assumption analysis method, simple linear regression, hypotheses and processed with SPPS software version 25. The results of this research show that the acquisition of the t test results is tcount (2.492) > ttable value, (2.085). The result of the test for the coefficient of determination is the R square of 0.220 (22%). Which means that murabahah receivables have an influence of 22% on the net profit of Bank Syariah Indonesia (BSI). The hypothesis states that murabahah receivables (Variable X) have a positive and significant effect on net income (Variable Y).